Thyroid Dysfunction and Sleep Disorders - Green, Max E.; Bernet, Victor; Cheung, Joseph (Frontiers in Endocrinology, 2021)
Thyroid disorders and sleep disorders are common problems in the general population that can affect people of all ages, backgrounds, and sexes, but little is known about their clinical associations. We reviewed the literature assessing the associations between thyroid disease and sleep disorders and noted that hyperthyroidism and hypothyroidism have clinical overlap with sleep conditions such as insomnia, restless legs syndrome, and obstructive sleep apnea. These findings highlight the importance of identifying and managing thyroid dysfunction for patients with these common sleep disorders. Additional research is needed to further understand how thyroid dysfunction affects sleep physiology.